Subject Authentication using Time-Frequency Image Textural Features - Alotaiby, Turky N.; Alshebeili, Saleh A.; Alotibi, Gaseb (2021 International Conference on Artificial Intelligence in Information and Communication (ICAIIC), 2021)
The growing internet-based services such as banking and shopping have brought both ease to human's lives and challenges in user identity authentication. Different methods have been investigated for user authentication such as retina, finger print, and face recognition. This study introduces a photoplethysmogram (PPG) based user identity authentication relying on textural features extracted from time-frequency image. The PPG signal is segmented into segments and each segment is transformed into time-frequency domain using continuous wavelet transform (CWT). Then, the textural features are extracted from the time-frequency images using Haralick's method. Finally, a classifier is employed for identity authentication purposes. The proposed system achieved an average accuracy of 99.14% and 99.9% with segment lengths of one and tweeny seconds, respectively, using random forest classifier.